Development of a scale of sensitivity to criticism in a group of students of Lima, Peru - León-Donayre, Ramón (2005)
The present communication informs about the construction and validation process of a psychometric reactive which evaluates the sensitivity to criticism, a psychological construct of inmense importance in the clinic, educational and organizational psychology. The authors constructed a 20-items reactive with topics as the zone of residence, the social abilities, academic achievement, and some other characteristics, to be evaluated with a Likert-Scale (0 to 10) as a motive of critic by close friends. The subjects were asked to response to what extent were they hurt by this critic.